Performance of agricultural tractors in traction - Serrano, João Manuel Pereira Ramalho (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the performance of agricultural tractors and tillage implements. Also, it was sought to establish mathematical models to estimate the draught requirement of disc harrows, and to validate the relationship between fuel consumption per hectare and the specific drawbar pull. The data acquisition system developed to use in field tests, under real working conditions, permitted the measure of following performance parameters: engine speed, theoretical and actual forward speed, fuel consumption per hour and drawbar pull. Tests were also made with a power take-off dynamometer. The results of a three years research project were used to establish a mathematical model to estimate the draught requirement of the disc harrows, valid for dry, undisturbed loam soils, and to validate the linear relationship between the drawbar pull per unit of implement width and the fuel consumption per hectare, which indicates the tractor-implement dimensioning. The data also put in evidence the benefits of the "gear up, throttle down" approach.